Engineering "cell-particle hybrids" of pancreatic islets and bioadhesive FK506-loaded polymeric microspheres for local immunomodulation in xenogeneic islet transplantation. (November 2019) - Nguyen, Tiep Tien; Pham, Tung Thanh; Nguyen, Hanh Thuy; Nepal, Mahesh Raj; Phung, Cao Dai; You, Zhiwei; Katila, Nikita; Pun, Nirmala Tillija; Jeong, Tae Cheon; Choi, Dong-Young; Park, Pil-Hoon; Yong, Chul Soon; et al.
Abstract: Host immune response remains an obstacle in cell-replacement therapy for treating type I diabetes. Long-term systemic immunosuppression results in suboptimal efficacy and adverse reactions. Thus, "cell-particle hybrids" of pancreatic islets and tissue-adhesive, polydopamine-coated, FK506-loaded biodegradable microspheres (PD-FK506-MS) were developed to locally modulate the immune response at the transplantation site. Coating of FK506-MS with PD enabled the rapid formation of stable cell-particle hybrids without significant changes in islet viability and functionality. Extremely low quantities of FK506 (approximately 600 ng per recipient) sustainably released from cell-particle hybrids effectively prolonged survival of xenogeneic islet graft. Interestingly, FK506 exhibited extended bioavailability in the grafts but was undetectable in systemic circulation and other tissues. Moreover, mRNA expression of inflammatory cytokines was significantly inhibited in the PD-FK506-MS-containing grafts but not in lymphoid organs. This study presents a promising platform that facilitates the translation of local immunomodulation towards an effective strategy with improved safety profiles for treating type I diabetes.